"Analyzing of the economic relationship between Dutch disease and the disruption of the Iraq economic structure " - صالح لورنس يحيى; ثامر جبار كريم (Journal of Economics and Administrative Sciences, 2019)
The status of the semi total stoppage and non-use and waste of economic made studying and analyzing Dutch disease of high importance because it is a major cause in aggravation of this status which happened to the Iraqi economy in almost complete way and the relative big importance that oil source has and its domination on the largest percentage in the gross domestic product and exports that Iraqi economy is relying largely in funding the national budget made the concentration of the study on this subject an important and necessary within the important economic events that Iraqi economy witnessed after 2003 till 2016 to give a clear and an overall picture of the reality of the unilateral Iraqi economy under the status of semi total and the nonuse of economic resources and the waste of development opportunities and not using them in an efficient way and the clear and big declining in economic sectors and the absent of their role in varying the income sources in the Iraqi economy which suffered and still suffering of Dutch disease that this study tackles its concept, causes and examining the reflections in wasting the economic resources and wasting the rights of the coming generations that has been through explaining the relationship which explores the cause and the result among the research variables that Dutch disease is a cause leads to wasting of resources as a must result by using the theoretical style enhancing these results with standard and statistical styles to stand on the size of the relationship between the two variables reaching a realistic results which indicated that Iraqi economy and relaying on oil resource as an essential and major resource in providing financial resources for managing the country and supporting state of unilateral economy. The study also tackled some strategic suggestions of treatment from the Dutch Disease in the Iraqi economy and heading towards the right direction to vary the income sources.